Nanoscale and mechanical properties of the physiological cell-ECM microenvironment - Young, Jennifer; Holle, Andrew W.; Spatz, Joachim P. (Experimental cell research, 2016)
Studying biological processes in vitro requires faithful and successful reconstitution of the in vivo extracellular matrix (ECM) microenvironment. However, the physiological basis behind in vitro studies is often forgotten or ignored. A number of diverse cell-ECM interactions have been characterized throughout the body and in disease, reflecting the heterogeneous nature of cell niches. Recently, a greater emphasis has been placed on characterizing both the chemical and physical characteristics of the ECM and subsequently mimicking these properties in the lab. Herein, we describe physiological measurement techniques and reported values for the three main physical aspects of the ECM: tissue stiffness, topography, and ligand presentation.